Accurate Laboratory Measurement of the O2 Collision‐Induced Absorption Band Near 1.27 μm. Issue 1 (8th January 2019) - Mondelain, D.; Kassi, S.; Campargue, A.
Abstract: The atmospheric band of O2 near 1.27 μm plays an important role in determining the air mass from ground or spaceborne atmospheric spectra. This band consists of narrow absorption lines of the a Δ 1 g − X Σ g − 3 0 − 0 transitions superimposed to a much broader collision‐induced absorption (CIA) structure. Very accurate CIA binary coefficients, B O 2 − O 2, B O 2 − N 2, and B O 2 − air, are determined by highly sensitive cavity ring down spectroscopy from low density spectra (0.36 to 0.85 amagat) of pure oxygen and an O2 /N2 mixture (20.96%/79.04%) at room temperature over the 7, 513–8, 466‐cm −1 region. Two cavity ring down spectrometers involving 12 distributed feedback lasers and two external cavity diode lasers were used below and above 7, 920 cm −1, respectively. The measurements performed at different densities show a percent level consistency. This accuracy results from (i) a high baseline stability of the spectra, (ii) an accurate determination of the baseline using argon spectra recorded for the same densities, and (iii) a reliable removal of the local contribution of the absorption lines made easier thanks to subatmospheric pressure recordings. The retrieved binary coefficients are compared to the experimental data included in HITRAN2016 database (Maté et al., 1999, https://doi.org/10.1029/1999JD900824 ), to the dataset used for Total Carbon Column Observing Network spectra as well as to recent ab initio calculations. Although more accurate, the binary coefficients reported here are found in agreement with the Maté et al. measurements using high pressure Fourier transform spectroscopy. The derived value of the integrated CIA band intensity S O 2 − air = 1.31(3) × 10 −4  cm −2 amagat −2 exceeds the corresponding Fourier transform spectroscopy value by about 3%. Key Points: Collision‐induced absorption of 1.27‐μm O2 band is measured with unprecedented accuracy by highly sensitive cavity ring down spectroscopy Accurate determination of the binary coefficients is achieved at room temperature with pure oxygen and a mixture of oxygen and nitrogen